Strategi Digital untuk Agripreneur 4.0: Meningkatkan Pemasaran, Penjualan, dan Branding dalam Agribisnis - Hendra, Acep; Habibi, Chairul; Ramadan, Diki; Mikala, Azka Khafifan (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
The development of digital technology presents both challenges and significant opportunities for the agribusiness sector in Indonesia, especially for farmers and small-scale agribusiness entrepreneurs. This community service initiative aims to provide understanding and skills related to digital strategies in marketing, sales, and branding to strengthen the competitiveness of agribusiness products. Through training and mentoring at SMKN PP Lembang, participants are empowered to leverage digital technology, such as social media marketing, SEO optimization, and the use of e-commerce platforms to expand their market reach and increase agribusiness sales. The results of this activity show an increased understanding among participants of the importance of digitalization in agribusiness and the implementation of effective marketing strategies to introduce products to a broader consumer base. However, key challenges faced include limited infrastructure and low digital literacy among some farmers and agribusiness actors. Therefore, ongoing support from the government and private sectors in terms of infrastructure and training is essential to support the digital transformation of the agribusiness sector.